Association of dietary intake of n-3 polyunsaturated fatty acids with breast cancer risk in pre- and postmenopausal Chinese women. Issue 8 (August 2022) - Zhang, Zhuo-Lin; Ho, Suzanne C; Liu, Kai-Yan; Mo, Xiong-Fei; Feng, Xiao-Li; Li, Lei; Zhang, Cai-Xia
Abstract: Objective: This study aimed to evaluate the associations between breast cancer risk and intake of n-3 polyunsaturated fatty acids (PUFAs) and/or n-3 PUFA subclasses in Chinese women, and determine whether these associations varied with menopausal status or clinical characteristics. Methods: A hospital-based case-control study including 1, 589 cases and 1, 621 age-frequency-matched controls was conducted. Dietary data were assessed by a validated food frequency questionnaire. Odds ratios (ORs) and 95% confidence intervals were obtained using multiple unconditional logistic regression models after controlling for potential confounders. Results: Higher intake of marine n-3 PUFAs and total n-3 PUFAs was associated with lower risk of breast cancer, with adjusted OR quartile 4 v.1 (95% confidence intervals) of 0.68 (0.55-0.84) and 0.56 (0.42-0.75), respectively. Dietary a-linolenic acid, eicosapentaenoic acid, docosapentaenoic acid, docosahexaenoic acid were also inversely associated with breast cancer risk, with adjusted ORs (95% confidence intervals) of 0.51 (0.38-0.70), 0.68 (0.55-0.84), 0.68 (0.55-0.85), and 0.76 (0.61-0.94), respectively. In stratified analyses, these inverse associations between risk and dietary n-3 PUFAs were more evident among premenopausal women and women with ER+, PR+ and ER+PR+ tumors. A decreased risk of breast cancer was significantly associated with increasing n-3 PUFA intake in obese/overweight women, but not in women of normal weight. There was a significant interaction between linoleic acid and marine n-3 PUFAs. Conclusions: High intake of n-3 PUFAs and n-3 PUFA subtypes was associated with a lower risk of breast cancer, especially among premenopausal women and women with ER+ and/or PR+ subtype breast cancer.